Hierarchical architectures in the third-generation cellular network. - Xiaoxin Wu (IEEE Wireless communications)
Third-generation wireless communication faces the challenges of rapidly increasing mobile user demand against limited radio bandwidth. Splitting cells into smaller cells can reduce the frequency reuse distance to improve network capacity within a certain area. Other than increasing the cost of the fixed infrastructure, cell splitting also causes the problem of increasing handoff rate and event the handoff failure rate when high-speed users roam in the network. To solve this problem, larger cells are overlaid on these smaller cells, and different classes of users (usually classified by speed) are initially assigned to the proper types of cells (i.e., proper tiers). We call this kind of cellular network a hierarchical cellular network. In this study, we review the different design techniques in the hierarchical architecture and some analytical tools to study the performance of these designs.